A Hybrid Piezoelectric and Triboelectric Nanogenerator with PVDF Nanoparticles and Leaf‐Shaped Microstructure PTFE Film for Scavenging Mechanical Energy. Issue 2 (27th November 2017) - Zhu, Jianxiong; Zhu, Yali; Wang, Xiaohu
Abstract: In this paper, a hybrid of piezoelectric polyvinylidene fluoride (PVDF)/polytetrafluoroethylene (PTFE) compound film and triboelectric leaf‐shaped microstructure film for mechanical energy harvesting is first reported. The nanoparticles compound film is designed with PVDF particles and leaf‐shaped PTFE. The triboelectric nanogenerator (TENG) is positioned at the upper side of the prototype and the piezoelectric nanogenerator (PENG) is placed at the lower side. It is found that the designed PENG could greatly enhance the harvested power by a coupling effect of PVDF nanoparticles and the compound PVDF/PTFE film than commercial film, and the leaf‐shaped PTFE film could benefit the electric output for the TENG. The average output power density of TENG and PENG can achieve 2.75 and 0.15 mW m −2 with resistor 300 MΩ, respectively. It is found that with the increasing external accelerations on prototype, the maximum generated output voltage by this mechanic‐electric conversion could obtain around 55 and −5.6 V by the two peak values, respectively. In the end, a random test using finger tap to light eight light‐emitting diodes is demonstrated the mechanical energy conversion performance of the TENG and PENG with the generated peak voltage of TENG and PENG 25 and −5.2 V, respectively. Abstract : A hybrid piezoelectric and triboelectric nanogenerator with polyvinylidene fluoride (PVDF) nanoparticles and leaf‐shaped microstructure polytetrafluoroethylene (PTFE) film is developed for scavenging mechanical energy harvesting. The coupling effect of PVDF nanoparticles and the compound PVDF/PTFE film can greatly enhance the harvested power to piezoelectric nanogenerator (PENG), and the leaf‐shaped PTFE film benefit the electric output from the triboelectric nanogenerator (TENG).